Il transfert di Curial. - COMPAGNA, ANNA MARIA (Scripta)
The supranational implications found in the three protagonists of the novels in the "Catalan quattrocento" (Jacob Xalabín, Curial and Tirant) allow an analysis of Curial e Güelfa that underlines the multiple identity and cultural openness of the protagonist's training process, in his economic and social rise. The evolution of the protagonist, thank to a psychological mechanism, now recognized as such, allows the happy ending of the novel, unlike what happens in the other two, where the protagonists, Jacob and Tirante, always remain the same. Thanks to the movement, to the transfert, Curial does not eliminate what threatens it, but manages to overcome it, if it is another individual, and this allows its final success, without being the victim of unacceptable internal impulses.